Penerapan Model Pembelajaran Problem Based Learning di Kelas VI Sekolah Dasar - Rida Eko Mujiwati (Universitas Sebelas Maret, 2020)
Problem Based Learning (PBL) learning model is a problem-based learning that requires students to think critically, logically, and can solve all the problems they experience. understand concepts, meanings, and relationships through the existence of problems to finally arrive at a solution. Problems occur when individuals are involved in social interactions both with the environment and with other people. There is a mental process to find several solutions and solutions to the problem. Problem Based Learning is a series of learning activities in which there are several activities that must be carried out by students. In Improving student learning outcomes through the Problem Based Learning Learning Model, teachers and students of Khaira Ummah Padang Islamic Elementary School in the 2019/2020 academic year are more active and interested and feel responsible and can be seen from student learning outcomes that have increased from each stage. learning.